2020
DOI: 10.24831/jai.v48i2.29784
|View full text |Cite
|
Sign up to set email alerts
|

Produktivitas Tanaman Trichanthera gigantea pada Berbagai Taraf Naungan dan Pupuk Kandang Kelinci

Abstract: Sebagian besar tanaman pakan ternak (TPT) dikembangkan di lahan marjinal dan integrasi dengan tanaman pangan maupun perkebunan. Trichantera gigantea (TG) merupakan tanaman pakan ternak (TPT) yang termasuk legum pohon dengan kandungan nutrisi cukup baik dan toleran naungan. Tujuan penelitian ini untuk mengetahui pengaruh interaksi antara naungan dengan pemberian pupuk kandang terhadap produktivitas dan karakteristik pertumbuhan tanaman Trichantera gigantea (TG). Rancangan yang digunakan adalah rancangan acak ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Low light intensity stimulates the plant to produce more leaves to capture the light, so the photosynthesis process can be done as needed. Herdiawan and Harmini, (2020) reported that shading treatment on Trichanthera gigantea resulted in more leaves than control. The grass without fertilizer has 23.94 leaves, while the grass with fertilizer has 38.20 leaves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low light intensity stimulates the plant to produce more leaves to capture the light, so the photosynthesis process can be done as needed. Herdiawan and Harmini, (2020) reported that shading treatment on Trichanthera gigantea resulted in more leaves than control. The grass without fertilizer has 23.94 leaves, while the grass with fertilizer has 38.20 leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Organic fertilizers will improve soil structure, texture, and pores, increasing the soil's water-holding capacity (Zulkarnain et al, 2013). Providing fertilizer that contains nitrogen (N), phosphor (P), and potassium (K) to the grass has a positive effect on the number of leaves, tillers, chlorophyll content, root volume, and dry matter (DM) content (Herdiawan and Harmini, 2020). Both organic and inorganic fertilizers provide essential nutrients for the plant.…”
Section: Introductionmentioning
confidence: 99%